Dinner at the center of the earth ebook A novel. - Englander, Nathan (2017)
A political thriller set against the Israeli-Palestinian conflict, from the Pulitzer-nominated, bestselling author of  For the Relief of Unbearable Urges.  A  Los Angeles Times  Best Book of the Year   “Blends elements of spy thriller and love story, magical realism, and an all-too-real history of one of the world’s most intractable problems: peace between Israel and its neighbors." — The Boston Globe In the Negev desert, a nameless prisoner languishes in a secret cell, his only companion the guard who has watched over him for a dozen years. Meanwhile, the prisoner’s arch nemesis—The General, Israel’s most controversial leader—lies dying in a hospital bed. From Israel and Gaza to Paris, Italy, and America, Englander provides a kaleidoscopic view of the prisoner’s unlikely journey to his cell.  Dinner at the Center of the Earth is a tour de force—a powerful, wryly funny, intensely suspenseful portrait of a nation riven by insoluble conflict, and the man who improbably lands at the center of it all.